An Assessment of the Knowledge of Dentists on the Emergency Management of Avulsed Teeth - ŞEN YAVUZ, BETÜL; KARGÜL, BETÜL (UNIV ZAGREB, SCH DENTAL MEDICINE, 2020)
Objective: to investigate the knowledge and attitudes of general dental practitioners (GDPs) on the emergency management of avulsed teeth. The management of the avulsed teeth is well outlined in the latest trauma guideline. However, little information is available about the level of knowledge of the management of avulsed teeth among young dentists in Turkey. Material and Methods: A cross-sectional questionnaire was completed to assess the knowledge of GDPs on the emergency management of avulsed teeth. The questionnaire asked questions to 142 dental practitioners about whether they have received information about the emergency management of dental trauma, whether they have intervened in cases of avulsed teeth following a dental trauma, and, finally, whether they have given treatment of avulsed teeth. Results: The majority of GDPs had received training to treat avulsed teeth. The findings of the study showed that only 35% of GDPs recalled the critical time for treatment. The number of GDPs who had incorrect knowledge on this topic was higher and statistically significant (p < 0.001). The rates of the correct answers according to the relevant information fields were as follows: optimal storage medium (7 8%) , type of splint (56%), splinting period (58.5%), and systemic medication after avulsion (32%). Conclusion: The results show that many GDPs had limited experience in treating avulsed teeth. However, in the study, it was stressed that the knowledge of GDPs related to the factors affecting the successful treatment of avulsion cases should be improved by using continuing education programs.
Keywords: Dental Trauma; Tooth Avulsion; Emergency Treatment; Tooth Replantation; Health Knowledge Attitudes Practice; Dentist's Practice Patterns; TRAUMATIC DENTAL INJURIES